Ukrainians In the Labor Market in Poland: Impact of The Covid-19 Pandemic on The Features of Their Employment - Aleksandra KUZIOR; Alla LOBANOVA (Communications of International Proceedings, 2021)
The aim of the work is to analyse the peculiarities of employment of Ukrainians in the Polish labor market before, at the beginning and during the Covid-19 pandemic. On the basis of theoretical and empirical methods the analysis of the modern labor market in Poland and Ukraine is carried out, in particular problems and challenges which exist on them are revealed, the reasons for which Ukrainians migrate to Poland, the intensity of migration flows before, at the beginning and during the pandemic was analyzed. It has been found that before, the pandemic, on the Polish labor market, there was a lack of employees with the low- and medium-level qualification, because about 2.5 million Poles went to work in other countries. Therefore, the demand for Ukrainian labor force was natural and logical. Before the pandemic, Poland legally employed more than 900,000 Ukrainian workers for working in the sectors of agriculture, construction, industry and services. During the period of quarantine measures and the closure of borders, around 500,000 Ukrainians returned to Ukraine, about the same number remained in Poland. The forecast is substantiated that after the end of the quarantine to prevent the spread of the Covid-19 pandemic and the opening of borders in the Polish labor market, there will be vacancies for low- and medium-skilled workers who can replace Ukrainian workers.
Keywords: coronavirus pandemic; labor market; labor migration; workers